Post liver transplantation complications in pediatric patients in a third level hospital, Lima-Peru, 2016-2020 - Castro-Johanson, Rosa (2024)
Objective: determine the complications during the first year after liver transplantation in pediatric patients of the INSN-SB during the period 2016-2020. Materials and methods: Descriptive, cross-sectional study. The medical records of liver transplant patients seen during post-transplant follow-up at the INSN-SB were reviewed, collecting epidemiological characteristics, transplant indication; PELD score, CHILD score and complications prior to the transplant, as well as the frequency of the main complications presented during the first year after the transplant. Results: Of the 16 patients evaluated, 62.5% were under 1 year of age, with a median weight of 7.4kg, 50% presented a CHILD C score, with a median PELD of 23, the main reason for transplantation was atresia of bile ducts (62.5%), the main complications prior to transplantation were portal hypertension (75%) and malnutrition (68.8%). All posttransplant patients presented at least one infectious complication: bacterial (53%), CMV infection (75%) and EBV infection (31%); Regarding vascular complications, 25% presented portal vein thrombosis and one patient (6%) presented hepatic artery stenosis; Regarding biliary complications, 12.5% presented biliary fistula, also 12.5% presented bile duct dilation, while 6.25% presented bilioma. Conclusions: Among the main complications of the postliver transplant patient, we can highlight that all patients presented at least one infectious complication (100%), vascular complications in 31% and biliary complications in 31.25% of patients.